Factors affecting rubber prices: From the perspective of Malaysian rubber smallholders - Nik Mohd Rashid, Nik Mohd Norfadzilah; -, Aripin; -, R.M.a; -, Hamid (2010)
This paper aims to determine the factors affecting the prices of natural rubber in Peninsular Malaysia from the rubber smallholders ' point of view. Natural rubber prices may be affected by type of government incentive, aid to rubber plants and factors affecting rubber cultivation. The data used for this study is from questionnaires distributed to rubber tappers regardless of background in Selangor and Perak. Only 68 respondents out of 150 completed their questionnaires. The multiple and descriptive analysis were employed to between the independent variables and price of natural rubber. The findings shown that rubber cultivation and type of incentive from the government impact natural rubber price. However, assistance for rubber plants failed to affect the rubber price. In summary the reduction of prices and poof performance in the market was led the rubber tappers to the financial distress condition. Meanwhile, with unreasonable outcome from this scenario it was also contribute to difficult situation. Therefore, the corporate sectors should actively involve in improving rubber tapper’s household income.